A sodium acetate trihydrate-formamide/expanded perlite composite with high latent heat and suitable phase change temperatures for use in building roof. (30th November 2019) - Huang, Rui; Feng, Jinxin; Ling, Ziye; Fang, Xiaoming; Zhang, Zhengguo
Highlights: A novel expanded perlite based composite phase change material (PCM) is developed. A sodium acetate trihydrate-formamide mixture is used as the PCM. The supercooling degree of the mixture is reduced by adding a nucleating agent. The composite PCM has a melting point of 40.5 °C and an enthalpy of 148.3 J/g. A good thermal performance is achieved by the composite PCM when applied in roof. Abstract: Introducing a phase change material (PCM) with large latent heat, low thermal conductivity, and appropriate phase change temperatures into building roof favors reducing indoor temperature fluctuation and increasing thermal comfort, thus helping to realize building energy conservation. Herein, a sodium acetate trihydrate (SAT)-formamide (FA) mixture was combined with expanded perlite (EP) to prepare a novel composite PCM. It is shown that adding tetrasodium pyrophosphate decahydrate at a loading of 3 wt% can reduce the supercooling degree of the mixture from 34.5 °C to 0.4 °C. The obtained mixture, composed of 77.6 wt% of sodium acetate trihydrate, 19.4 wt% of formamide and 3 wt% of tetrasodium pyrophosphate decahydrate, can be absorbed into EP to prepare a form-stable composite PCM at a mass fraction of 55 wt%, which has a melting point of 40.5 °C and an enthalpy of as large as 148.3 J/g. This composite PCM possesses good thermal reliability and has a thermal conductivity of as low as 0.0978 W/(m·K). The thermal performance of the composite PCM when employed in the roof of a test room was investigated and compared with those of the previously reported CaCl2 ·6H2 O/EP composite PCM and EP. It is found that, the test room with the SAT-FA/EP composite in the roof exhibits slower temperature rise and drop rates, a reduction in the highest temperature, and an increase in thermal comfort, compared with those containing the CaCl2 ·6H2 O/EP composite PCM and EP. The better thermal performance of the SAT-FA/EP composite is attributed to its larger latent heat and more suitable phase change temperatures for use in roof, thereby showing great potential for practical applications.